2015
DOI: 10.1039/c4nj02094d
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation on toluene-3,4-dithiolatoantimony(iii) alkyldithiocarbonate complexes: thermal, powder XRD and biological studies

Abstract: On thermal decomposition of the mixed sulfur donor antimony(iii) complexes, we obtained antimony sulfide at 600 °C, which was confirmed by scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDAX).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…00–042‐1759 and 00–070‐1332. It has been observed that the complexes have a crystalline structure, nanometric particles sizes of 14.67 and 11.39 nm characteristic of nanoparticles, lower symmetry (monoclinic) with unit cell volume of 4968.47 and 5079.79 Å 3 and have been calculated using the following formulae: 1d2=1sin2β()h2a2+k2sin2βb2+l2c22italichklcosβac V=italicabcsinβ …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…00–042‐1759 and 00–070‐1332. It has been observed that the complexes have a crystalline structure, nanometric particles sizes of 14.67 and 11.39 nm characteristic of nanoparticles, lower symmetry (monoclinic) with unit cell volume of 4968.47 and 5079.79 Å 3 and have been calculated using the following formulae: 1d2=1sin2β()h2a2+k2sin2βb2+l2c22italichklcosβac V=italicabcsinβ …”
Section: Resultsmentioning
confidence: 72%
“…The presence of a lone pair of electrons on the metal present in the complexes which does not take part in the bonding results in a distorted octahedral geometry, due to which the complexes have lower symmetry (monoclinic). The mean crystallite size can be determined from the full width at half maximum of the diffraction peaks using the Debye–Scherrer formula: D=Bcosθ where D is the particle size, K a constant whose value is approximately 0.9, λ the wavelength of the X‐rays, B the full width at half maximum and θ the Bragg angle.…”
Section: Resultsmentioning
confidence: 99%
“…Dithiocarbamates are a class of metal‐chelating, antioxidant compounds with various applications in chemistry, industry, agriculture and medicine for treatment of bacterial and fungal infection and possible treatment in AIDS; pyrrolidine iron dithiocarbamate derivatives were considered for treatment of AIDS as they can potently block a transcription factor involved in HIV . Antimony sulfur complexes have many potential applications in various fields such as thermoelectric cooling technologies, solar energy conversion, optoelectronic devices and microwave devices due to their semiconducting property . Dithiocarbamates stabilize high oxidation states in metal complexes, reflecting strong o‐bonding characteristic of dithiocarbamates in which there is an additional n‐electron flow from nitrogen to sulphur via planar delocalized π‐orbital system, as shown below: …”
Section: Introductionmentioning
confidence: 99%
“…(2)(b),(d) and (f), which might be related to the particle shapes, which disperse light allowing very small light reflection. The EDAX spectrum of antimony nanoparticles deposited on copper substrate appeared as M α and L α at (0.4 and 3.6) Kev as compared with standard values from energy table for EDAX analysis and as reported by H.Chauhan and coworkers [14], shown in Figure (3).The EDAX analysis confirmed the presence of small amounts of antimony with 3.47 At.%, 3.95At.% and 4.47At.% at one, two and three hours samples respectively. AFM images of the electrodeposited antimony are shown in Fig.(4).…”
Section: Fig(1): Cyclovoltammogram Of Saturated Solution (03m) Sbclmentioning
confidence: 99%